Higher plants as bioindicators of sulphur dioxide emissions in urban environments. - Hijano, Concepción Fidalgo; Domínguez, Maria Dolores Petit; Gimínez, Rosario García; Sínchez, Pilar Hungría; García, Inís Sancho (Environmental monitoring and assessment, 2005)
The evaluation of certain vascular plants that grow in the city of Madrid as biomonitors of SO(2) air pollution in urban environments has been carried out. Total concentration of sulphur in leaves of the chosen higher plants as well as other parameters in close relation to this contaminant (visible injury symptoms, chlorophyll a- and b-content and peroxidase activity) have been determined in order to study the spatial distribution and temporal changes in SO(2) deposition. Results obtained show that coniferous species such as Pinus pinea, were more sensitive to SO(2) atmospheric concentration than leafy species as Quercux ilex subspecies ballota and, in the same way, bush species, such as Pyracantha coccinea and Nerium oleander, were more sensitive than wooded species, such as Cedrus deodara and Pinus pinea, respectively. There is a higher accumulation of sulphur in vegetable species located near highways and dense traffic incidence roads and near areas with high density of population. The minimum values for accumulation of SO(2) were registered in winter and spring seasons (from January to April) due to the vegetative stop; while maximum values are obtained during the summer season (from June to September), due to the stoma opening. The highest increments in sulphur concentration, calculated as the difference between two consecutive months, are obtained in May and June for all considered species except for Cedrus deodara and Pyracantha coccinea, both species have few seasonal changes during the whole year. Some species are more sensitive to natural washing than others, showing a decrease in sulphur concentration after rainfall periods.
Keywords: atmospheric pollution; Bioindicators; Cedrus deodara; higher plants; Nerium oleander; Pinus pinea; Pyracantha coccinea; Quercus ilex; Sulphur dioxide

Effects of sulphurous gases in two CO2 springs on total sulphur and thiols in acorns and oak seedlings - Grill, D; Müller, M; Tausz, M; Strnad, B; Wonisch, A; Raschi, A (Atmospheric Environment, 2004)
Quercus ilex and Quercus pubescens acorns were collected at two CO2 springs in Tuscany (Bossoleto and Viterbo, resp.). In addition to elevated CO2, these springs are a source of H2S and SO2 . Acorns from a comparable ﬁeld site distant from CO2 springs were used as controls. Acorns from CO2 springs contained signiﬁcantly higher sulphur concentrations than controls (0.67 vs. 0.47 mg g 1 dw in Q. ilex cotyledons and 1.01 vs. 0.80 in Q. pubescens) and, in Q. ilex, also more glutathione (1634 vs. 1393 nmol g 1 dw). When acorns were germinated and seedlings grown under ambient air conditions in the Botanical Garden in Graz for one year, leaves of Q. pubescens grown from CO2 spring acorns showed signiﬁcantly higher S-concentrations than leaves grown from control acorns (2.27 mg g 1 vs. 1.56 mg g 1 dw), and those of Q. ilex higher glutathione concentrations (929 vs. 462 nmol g 1 dw, CO2 spring vs. control acorns). One-year-old Q. ilex seedlings grown from CO2 spring acorns also showed elevated rates of chromosomal aberrations in root tips (a widely used test for environmental impacts), suggesting a permanent stress situation of the seedlings originating from the CO2 springs.
Keywords: cytogenetic; Glutathione; hydrogen sulphide; Stress; Sulphur dioxide

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology